Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1192/bjp.bp.114.154997
|View full text |Cite
|
Sign up to set email alerts
|

Non-replication of the association between 5HTTLPR and response to psychological therapy for child anxiety disorders

Abstract: BackgroundWe previously reported an association between 5HTTLPR genotype and outcome following cognitive–behavioural therapy (CBT) in child anxiety (Cohort 1). Children homozygous for the low-expression short-allele showed more positive outcomes. Other similar studies have produced mixed results, with most reporting no association between genotype and CBT outcome.AimsTo replicate the association between 5HTTLPR and CBT outcome in child anxiety from the Genes for Treatment study (GxT Cohort 2, n = 829).MethodLo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 31 publications
0
20
0
2
Order By: Relevance
“…We have been studying genetic influences on outcome following psychological therapy in anxiety disorders. As with any area of psychiatric genetics, the work requires large sample sizes and most studies to date have been underpowered (e.g., work on pediatric anxiety 48 ). However there are preliminary indications that there are genetic influences on response to psychological treatment, 49 indicating that this is a fruitful avenue for further research.…”
Section: Discussionmentioning
confidence: 99%
“…We have been studying genetic influences on outcome following psychological therapy in anxiety disorders. As with any area of psychiatric genetics, the work requires large sample sizes and most studies to date have been underpowered (e.g., work on pediatric anxiety 48 ). However there are preliminary indications that there are genetic influences on response to psychological treatment, 49 indicating that this is a fruitful avenue for further research.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of genetic effects on symptoms may increase with age (Waszczuk, Zavos, Gregory, & Eley, ); ‘new’ sources of genetic influence may emerge at particular time points across adolescence (Waszczuk, Zavos, Gregory, & Eley, ); and finally, there may be shared genetic variance between anxiety and depression in youth (Waszczuk et al., ). Studies uncovering which genes are involved have revealed inconsistent findings with many candidate–gene association studies being unable to replicate initially promising associations between specific gene polymorphisms and behaviours, and more hypothesis‐free genome‐wide association studies failing to find associations that meet genome‐wide level significance (Lester et al., ; Trzaskowski et al., ). Despite these uncertain results, there have nonetheless been efforts to investigate how genetic vulnerability is expressed through more intermediate mechanisms to influence symptoms.…”
Section: A Brief Summary Of Distal Risk Factors For Anxiety and Deprementioning
confidence: 99%
“…All participants come from the Genes for Treatment (GxT) Study, an international multisite collaboration designed to identify predictors of outcome following CBT for child anxiety. [28,36]…”
Section: Participants Study Overviewmentioning
confidence: 99%
“…[24] The field of "therapygenetics" is a growing area of research focusing on genetic predictors of outcome in response to psychological therapies. [25] A small number of candidate genes have been implicated, focusing primarily on polymorphisms and epigenetic regulation of genes involved in brain-related markers, such as the serotonin transporter gene (SERT [26][27][28] ), brain-derived neurotrophic factor (BDNF [29] ), and nerve growth factor (NGF [30] ), among others. [31] One study has examined FKBP5 genotype with respect to therapy outcome, finding an association between the SNP rs1360780 and the effectiveness of narrative exposure therapy for PTSD (N = 43 [32] ).…”
Section: Introductionmentioning
confidence: 99%